Effects of postactivation potentiation on tennis serve velocity and accuracy - Terraza-Rebollo, M.; Baiget, E. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine the postactivation potentiation effect on serve velocity and accuracy in young competition tennis players using complex training, and comparing different upper and lower body heavy-load resistance exercises (HLRE). Methods: Fifteen competition tennis players (9 boys and 6 girls; age 15.6 [1.5] y) performed 1 control session and 3 experimental sessions using HLRE in a crossover randomized design: (1) bench press, (2) half squat, (3) bench press plus half squat, and (4) control trial. HLRE were performed by accomplishing 3 sets of 3 repetitions when bench press or half squat conditions were performed and 2 sets of 3 repetitions of each exercise when bench press plus half squat condition was performed at 80% 1-repetition maximum, lifting the load at maximum speed. To assess the serve velocity and accuracy, all participants performed 32 flat serves after the HLRE, divided into 4 sets of 8 serves (0, 5, 10, and 15 min postexercise), resting 20 seconds between serves, and 2 minutes and 40 seconds between sets. Results: There were no significant (P>.05) differences in ball velocity and accuracy following each recovery time and exercise, compared with the basal situation. Conclusions: These results suggest that complex training using HLRE is not a useful method for eliciting the postactivation potentiation effect in tennis serve and does not have any effect in serve accuracy in young competition tennis players.